Detection of trichothecene producing Fusarium spp. by PCR: adaptation, validation and application to fast food (Italian Journal of Public Health, 2005)
Background. Food contamination by trichothecene mycotoxins is considered to be an emerging publichealth problem. The aim of this study was to validate a rapid sonification protocol, previously set up forcereal Fusarium DNA extraction from fast food samples, produced by a centre for research and developmentin the food industry in Catania, Sicily, and to validate it for a diagnostic PCR assay targeted at tri5, the keygene of trichothecene biosynthesis.Methods. DNA from reference Fusarium spp. strains and from fast food samples was prepared, setting up anextraction protocol adapted using some modifications based on a method recently described. Validationexperiments were performed: serial dilution of DNA extracted from fungal cultures were added to foodsamples and then DNA was extracted. Specific primer pairs were used to detect F. graminearum and F.culmorum DNA in species-specific assays as well as trichothecene-producing Fusarium spp. in a group-specific system.Results. All genomic DNA extracted from trichothecene-producing Fusarium spp. as well as from DNA-spikedfast food samples and from food still in it’s original condition resulted in the correct amplification. Thedetection limit was 1 x 10-4μg of DNA. All fungal and food samples tested gave highly consistent results inrepeatability assays, thus demonstrating the within-lab and within/between-day precision of the method.Conclusions. Information on the epidemiology of trichothecene producing Fusarium through the food chainand the identification of the most frequently contaminated components of fast food are essential in order todevelop effective public health strategies for minimising consumer exposure to trichothecenes.
Keywords: Fusarium; fast food; trichothecenes; PCR